Determination of glyphosate and its metabolite in emergency room in Korea. (August 2016) - Han, Joseph; Moon, Hantae; Hong, Youngki; Yang, Songhee; Jeong, Won-joon; Lee, Kwang-Sik; Chung, Heesun
Highlights: A fast method to determine the concentration of glyphosate without derivatization is established by LC–MS/MS. The concentration of glyphosate and its metabolite from blood samples of intoxicated patients in emergency room is measured. The blood concentrations and clinical symptoms are not well correlated, possibly indicating effects of surfactants. The system that determines the blood concentration in advance can predict complications, which assists treatment. Abstract: The number of glyphosate intoxication cases has been increased after the regulation of paraquat. Unfortunately, there are no reports on the potential concentration of glyphosate for those acute intoxicated patients admitted to emergency rooms and the correlation between the concentration of glyphosate and clinical symptoms in Korea up to our knowledge. As a nonselective herbicide, analysis of glyphosate requires derivatization because of its amphoteric and strongly polar nature. In order to develop a method to determine the concentration of glyphosate and its metabolite, aminomethylphosphonic acid (AMPA) in blood samples without derivatization, liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS) was utilized with a hydrophilic interaction chromatography (HILIC) column. The validation of this method showed that the limits of detection (LODs) and limits of quantitation (LOQs) for glyphosate and AMPA were 50 and 100 ng/mL, respectively. In addition, matrix effect, recovery rate, and accuracy and precision in intra and inter-day were evaluated during the validation study of this method. Blood samples acquired from five glyphosate intoxicated patients were analyzed to investigate the correlation between the concentration of glyphosate and clinical symptoms. These patients were previously admitted to the emergency room at a University Hospital in Korea after glyphosate was self-administered in suicide attempts or by accident. As results of blood sample study, the concentration of glyphosate and AMPA were found in the range of 1.0–171.1 and 0.2–2.6 μg/mL, respectively. The concentration ratio of glyphosate to AMPA was 55–71. According to the clinical reports for those patients, they were in the age between 47 and 82 years old and administered about 50–400 mL. The blood samples were collected within 2–5 h after administration of glyphosate. Among the intoxicated patients, the most common clinical symptom was metabolic acidosis, identified in four patients. The comparison between the concentration of glyphosate and administered dosage did not show the correlation, which suggests further investigation on the effects of surfactants in glyphosate from different vendors.